2021
DOI: 10.1007/s00266-021-02611-x
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic Outcome of Gynecomastia Management with Conventional Liposuction and Cross-Chest Liposuction: A Prospective Comparative Study

Abstract: Background Liposuction is the most accepted technique for treatment of gynecomastia at present with or without residual gland tissue excision. Conventional liposuction uses incisions for introduction of cannula, made usually at the inframammary crease or axilla resulting in consequent scars. Cross-chest liposuction technique was introduced to avoid these additional scars and improve the aesthetic outcome. This study aimed to evaluate the difference between aesthetic outcome of conventional liposuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…This rate is higher compared to other published work. 18 , 19 Most patients (96.4%) in our study reported that they were more confident after their surgery. Similarly, most of the patients in our study were satisfied with the scar after surgery.…”
Section: Discussionmentioning
confidence: 59%
“…This rate is higher compared to other published work. 18 , 19 Most patients (96.4%) in our study reported that they were more confident after their surgery. Similarly, most of the patients in our study were satisfied with the scar after surgery.…”
Section: Discussionmentioning
confidence: 59%
“…Most of the patients in this study were overweight, as the mean body mass index was 27.94±1.93kg/m 2 , and more than one third of them were active smokers. Singamsetty R et al [23] in their comparative study of 30 patients found that the mean (SD) age of the patients was 22.6±4.13 years and almost all of patients had grade II gynecomastia, while Abdelrahman I et al [6] in their study of 18 patients observed that the mean age (SD) of the patients was 31 years (range: 28-34), and 61% of them had grade I gynecomastia, and their mean body mass index was 27.4kg/m 2 (range: 26.7-29.4).…”
Section: Discussionmentioning
confidence: 99%
“…Singamsetty et al (20) , en India (2022), en su estudio "Resultado estético de ginecomastia administración con liposucción convencional y liposucción cruzada de tórax", establecieron que con el manejo de ambos procedimientos quirúrgicos, presenta menos del 20 % tasas de complicaciones. De la misma manera, Lee et al (21) , en Corea del Sur (2022), en su estudio de casos y controles, revelan otro procedimiento con menos complicación que es la liposucción asistida por succión mural y portátil, donde pocos pacientes presentaron hematoma, seroma, infección de la herida.…”
Section: Discussionunclassified